PENGARUH PENAMBAHAN TEPUNG JAHE DALAM PAKAN TERHADAP KADAR LEMAK DAN PROTEIN DAGING AYAM BROILER - Syafitri, Novia; Brahmana, Eti Meirina; Karno, Ria (IAIN Batusangkar, 2018)
The purpose of this research was to know the influence of the addition of Ginger flour in the feed to the value of the levels of lipid and protein Broiler meat. These researches were conducted that used Soxhlet method to tested the lipid quality and Kjeldahl method to tested the protein. The sample were used Broiler aged 1 weeks up to 2 weeks, after 2 weeks old chicken was divided into 4 treatment groups of 6 each control group (P0) without treatment, P1 with addition of ginger flour in feed 2.5%, P2 in the addition of ginger flour in the diet of 5%, P3 with the addition of ginger flour in the feed as much as 7.5%. After 42 days old, Broiler conducted sampling of meat in the treatment for the examination of the levels of lipid and protein. The Data obtained are then analyzing used a One-way Anova. The result of these researches is in the range of lipid quality: P0 (8,33%), P1 (6,33%), P2 (5,25%), P3 (5,08%) After analyzed have done it shown there were differences that significance (p>0,05). Result of checked of protein quality: P0 (5,59%), P1 (5,32%), P2 (5,36%), P3 (5,45%) After analyzed were done there is no significance difference (p>0,05). The higher the percentage of ginger flour, the lower the fat content of broiler chicken.